HUBUNGAN PENGETAHUAN DAN SIKAP LANSIA DALAM PENANGANAN RHEUMATOID ARTRITIS DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI KOTA PEKANBARU - Muhamad Irwan; Emi Yulita; Rummy Islami Zalni (Ensiklopedia of Journal, 2023)
Arthritis is an autoimmune disease in which the pivot usually the hands and feet become inflamed, cause swelling, pain and often cause damage to the inside of the pivot. This think about investigates the relationship between information and states of mind of the elderly in taking care of Rheumatoid Arthritis within the work zone ofPayung Sekaki Wellbeing Center Pekanbaru City. This ponder may be a quantitative think about, the plan utilized in this inquire about is graphic correlative, specifically investigate to portray the knowledge and demeanors of the elderly approximately Rheumatoid pivot pain illness. The populace decided as inquire about subjects were all elderly individuals enduring from Rheumatoid Joint pain within the work region of the Payung Sekaki Wellbeing Center Pekanbaru City a test of 80 individuals who were taken by purposive inspecting strategy utilizing the level of information within the treatment of Rheumatoid pivot pain (p value <0.05) shows that there's a noteworthy relationship between demeanors within the treatment of Rheumatoid pivot pain.Keywords:Knowledge, Attitude, Rheumatoid Arthrits.